Nonlinear and vibrational microscopy for label-free characterization of amyloid-β plaques in Alzheimer's disease model. Issue 9 (23rd March 2021) - Cunha, Renan; Lafeta, Lucas; Fonseca, Emerson A.; Barbosa, Alexandre; Romano-Silva, Marco A.; Vieira, Rafael; Jorio, Ado; Malard, Leandro M.
Abstract : Multimodal optical imaging was used for characterization of amyloid-β plaques in mouse brain tissues. We obtained high-resolution images for different biomarkers and investigated vibrational fingerprints that could be used for diagnostic purposes. Abstract : Given the long subclinical stage of Alzheimer's disease (AD), the study of biomarkers is relevant both for early diagnosis and the fundamental understanding of the pathophysiology of AD. Biomarkers provided by Amyloid-β (Aβ) plaques have led to an increasing interest in characterizing this hallmark of AD due to its promising potential. In this work, we characterize Aβ plaques by label-free multimodal imaging: we combine two-photon excitation autofluorescence (TPEA), second harmonic generation (SHG), spontaneous Raman scattering (SpRS), coherent anti-Stokes Raman scattering (CARS), and stimulated Raman scattering (SRS) to describe and compare high-resolution images of Aβ plaques in brain tissues of an AD mouse model. Comparing single-laser techniques images, we discuss the origin of the SHG, which can be used to locate the plaque core reliably. We study both the core and the halo with vibrational microscopy and compare SpRS and SRS microscopies for different frequencies. We also combine SpRS spectroscopy with SRS microscopy and present two core biomarkers unexplored with SRS microscopy: phenylalanine and amide B. We provide high-resolution SRS images with the spatial distribution of these biomarkers in the plaque and compared them with images of the amide I distribution. The obtained spatial correlation corroborates the feasibility of these biomarkers in the study of Aβ plaques. Furthermore, since amide B enables rapid imaging, we discuss its potential as a novel fingerprint for diagnostic applications.